Growth factor transgenes interactively regulate articular chondrocytes12. Issue 4 (18th February 2013) - Shi, Shuiliang; Mercer, Scott; Eckert, George J.; Trippel, Stephen B.
Abstract Adult articular chondrocytes lack an effective repair response to correct damage from injury or osteoarthritis. Polypeptide growth factors that stimulate articular chondrocyte proliferation and cartilage matrix synthesis may augment this response. Gene transfer is a promising approach to delivering such factors. Multiple growth factor genes regulate these cell functions, but multiple growth factor gene transfer remains unexplored. We tested the hypothesis that multiple growth factor gene transfer selectively modulates articular chondrocyte proliferation and matrix synthesis. We tested the hypothesis by delivering combinations of the transgenes encoding insulin‐like growth factor I (IGF‐I), fibroblast growth factor‐2 (FGF‐2), transforming growth factor beta1 (TGF‐β1), bone morphogenetic protein‐2 (BMP‐2), and bone morphogenetic protien‐7 (BMP‐7) to articular chondrocytes and measured changes in the production of DNA, glycosaminoglycan, and collagen. The transgenes differentially regulated all these chondrocyte activities. In concert, the transgenes interacted to generate widely divergent responses from the cells. These interactions ranged from inhibitory to synergistic. The transgene pair encoding IGF‐I and FGF‐2 maximized cell proliferation. The three‐transgene group encoding IGF‐I, BMP‐2, and BMP‐7 maximized matrix production and also optimized the balance between cell proliferation and matrix production. These data demonstrate an approach to articular chondrocyte regulation that may be tailored to stimulate specific cell functions, and suggest that certain growth factor gene combinations have potential value for cell‐based articular cartilage repair. J. Cell. Biochem. 114: 908–919, 2013. © 2012 Wiley Periodicals, Inc.